Digital image correlation systems in the experimental investigations: capabilities and limitations - Krawczyk, Ł.; Gołdyn, Michał; Urban, Tadeusz (Archives of Civil Engineering, 2019)
The aim of the paper is to present the possibilities and limitations of using the Digital Image Correlation systems. In order to assess the measurement inaccuracies the measuring volume 1250 × 1100 mm was analysed using two cameras with sensor resolution 6 megapixels. It was stated very good accuracy of the line segment length change. It causes that observation of crack widths can be considered as precisely. Some practical information concern how determine the compatibility between crack width measured traditionally and by using DIC are given. In the second part of the paper the results of the tests concerning capacity of interface between two concrete casting at the same time were presented. Use of the optical measurement system Aramis enables the analysis of the deformation, determination of failure mode of the tested specimens and limit displacement between edges of the interface.
Keywords: Digital Image Correlation System; concrete structures; measuring systems